Effects of a Multidisciplinary Educational Rehabilitative Intervention in Breast Cancer Survivors: The Role of Body Image on Quality of Life Outcomes - Giovanni Morone; Marco Iosa; Augusto Fusco; Antonella Scappaticci; Maria Rosaria Alcuri; Vincenzo Maria Saraceni; Stefano Paolucci; Teresa Paolucci (The Scientific World Journal)
In breast cancer survivors, own body image may change due to physical and psychological reasons, worsening women’s living. The aim of the study was to investigate whether body image may affect the functional and quality of life outcomes after a multidisciplinary and educational rehabilitative intervention in sixty women with primary nonmetastatic breast cancer who have undergone conservative surgery. To assess the quality of life was administered The European Organization for Research and Treatment of Cancer Study Group on Quality of Life core questionnaire, while to investigate the psychological features and self-image were administered the following scales: the Body Image Scale, the Hamilton Rating Scale for Depression, and the State-Trait Anxiety Inventory. To assess the recovery of the function of the shoulder were administered: the Disabilities of the Arm, Shoulder, and Hand Questionnaire and the Constant-Murley Score. Data were collected at the baseline, at the end of the intervention, and at 3-month follow-up. We found a general improvement in the outcomes related to quality of life, and physical and psychological features after treatment (P < 0.001). During follow-up period, a higher further improvement in women without alterations in body image in respect of those with an altered self-perception of their own body was found (P = 0.01). In conclusion, the body image may influence the efficacy of a rehabilitative intervention, especially in the short term of follow-up.